Penerapan Metode Dmaic Untuk Meminimalisasi Ketidaksesuaian Stock Opname Antara Sistem Inventory Dengan Aktual Barang Di Perusahaan Retail Pada PT. Primafood International (Kios Unggas Cempaka) - Maryana, Tinih; Setyadi, Bakti; Sartika, Dewi (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
To ensure stock availability, PT. Primafood Internasional conducts stock taking every month, this study focuses on the analysis of inventory data discrepancies by identifying the main causes of deviations or differences in stock taking between written and physical quantities. Stock taking is a crucial process in inventory management that aims to ensure inventory records are in accordance with physical stock. However, discrepancies often occur which can cause financial losses and operational disruptions. This study aims to reduce stock taking discrepancies by using the DMAIC (Define, Measure, Analyze, Improve, Control) method. The results of this study indicate that there are several factors that cause stock taking discrepancies, namely human factors, system factors and environmental factors. The factors are that there are differences in goods from distributors, goods that have gone out have not been inputted, errors in inputting the number of goods coming into the system, expired goods and damaged goods have not been recorded, and the input system often has errors.